2020
DOI: 10.3390/antiox9060521
|View full text |Cite
|
Sign up to set email alerts
|

The Integrative Role of Sulforaphane in Preventing Inflammation, Oxidative Stress and Fatigue: A Review of a Potential Protective Phytochemical

Abstract: Cruciferous vegetables hold a myriad of bioactive molecules that are renowned for possessing unique medicinal benefits. Sulforaphane (SFN) is one of the potential nutraceuticals contained within cruciferous vegetables that is useful for improving health and diseased conditions. The objective of this review is to discuss the mechanistic role for SFN in preventing oxidative stress, fatigue, and inflammation. Direct and indirect research evidence is reported to identify the nontoxic dose of SFN for human trials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 98 publications
1
69
0
1
Order By: Relevance
“…One of the important pathways in this field is Nrf2-keap1 (nuclear factor erythroid 2-related factor 2-Kelch-like erythroid cell-derived protein with cap 'n' collar homology-associated protein 1) pathway. This pathway plays a major role in the expression of genes associated with maintaining cellular homeostasis and redox status, counteracting oxidizing molecules, and controlling cell functions such as apoptosis, differentiation, and cell proliferation [123,124]. In fact, under oxidative stress, Nrf2 within the nucleus interacts with antioxidant responsive element (ARE), leading to cell survival.…”
Section: Antioxidant Supplements As a Pro-oxidantmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the important pathways in this field is Nrf2-keap1 (nuclear factor erythroid 2-related factor 2-Kelch-like erythroid cell-derived protein with cap 'n' collar homology-associated protein 1) pathway. This pathway plays a major role in the expression of genes associated with maintaining cellular homeostasis and redox status, counteracting oxidizing molecules, and controlling cell functions such as apoptosis, differentiation, and cell proliferation [123,124]. In fact, under oxidative stress, Nrf2 within the nucleus interacts with antioxidant responsive element (ARE), leading to cell survival.…”
Section: Antioxidant Supplements As a Pro-oxidantmentioning
confidence: 99%
“…However, under hemostatic conditions, Nrf2 binds to the suppressor of the keap1 protein in the cytoplasm and is thus targeted by ubiquinine-dependent degradation in the proteasome [125,126]. On the other hand, many studies have recently concluded that Nrf2 can play an effective role in the prevention and treatment of diseases including exercise-induced organ damage and inflammation [122,123,126].…”
Section: Antioxidant Supplements As a Pro-oxidantmentioning
confidence: 99%
“…Of key importance to our discussion is the fact that phase 2 induction boosts the expression of both thioredoxin and thioredoxin reductase, as well as that of glutathione peroxidase, capable of eliminating hydrogen peroxide [ 61 , 62 , 63 , 64 , 65 ]. Nutraceutical phase 2 inducers that have shown important clinical utility include lipoic acid, ferulic acid, melatonin, and sulforaphane [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Nlrp3 Inflammasome Suppression Via Phase 2 Inductionmentioning
confidence: 99%
“…The biosynthesis of SFN occurs through a hydrolysis reaction that involves the myrosinase enzyme, present in plants, which together with the inactive form of epithiospecifier (ESP) protein leads to the formation of SFN. Conversely, the active form of ESP together with myrosinase leads to the synthesis of SFN nitrile [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%